PENGGUNAAN STRATEGI PENINGKATAN KEMAMPUAN BERPIKIR UNTUK MENGEMBANGKAN MODUL PEMBELAJARAN - Hima, Lina Rihatul; Santia, Ika (Jurnal Pembelajaran Matematika, 2018)
Abstract:This research is motivated by the existence of learning media that still unable to improve students' thinking skills. Learning media which is developed in this study are learning module. The learning module is expected to deepen students’ understanding of concepts and improve their ability to think critically. Module development uses one learning strategy that supports the research objectives. The strategy used is a strategy to improve thinking skill. Based on this background, the research questions are: (1) how is the development of learning module using thinking skill enhancement strategy? (2) How do students respond to the development of learning module using strategy for improving thinking skills? The development of learning module in this study uses ADDIE development model. This model has five stages of development, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study are seventh grade students of Private Junior High School (SMP) Wahidiyah Kediri. The instruments are in the form of learning module and students’ response questionnaires. The conclusions are: (1) The module is feasible and valid for students, and (2) Students’ response about the use of learning module is very good. Researchers’ suggestions for further development are: (1) learning module using thinking skill enhancement strategy needs to be completed in the form of content. concept, and design in order to create interesting and conducive learning atmosphere; (2) further development of other materials using thinking skill enhancement strategy is needed; and (3) further development refers to the latest curriculum used in educational institution, so that the learning module in line with the latest curriculum development..Keywords: Modules, Thinking Skill Enhancement Strategy.